Environmental factors influence yak milk composition by modulating short-chain fatty acid metabolism in intestinal microorganisms. (15th June 2022) - Zhang, Yaopeng; Zhao, Hongwen; Li, Qianqian; Tsechoe, Dorji; Yuan, Hongli; Su, Guijin; Yang, Jinshui
Abstract: In recent years, yak milk has received widespread attention due to its high nutrition, green and pollution-free characteristics, but the source of yak milk flavor is still unclear. In this study, fresh yak manure collected from Lhasa, Nagqu, Qamdo, Yushu, and Qinghai Lake were sequenced by 16S rRNA gene high-throughput sequencing technology. The correlation between intestinal microbiota and yak milk quality combined with the local environmental factors was evaluated for the first time. The enterotype of yaks from Lhasa, Nagqu, and Qinghai Lake was classified as enterotype of norank_f_Oscillospirales_UCG-010 and Rikenellaceae_ RC9_gut_group, and the enterotype of yaks from Qamdo and Yushu was classified as enterotype of Oscillospiraceae UCG-005 . Procrustes analysis showed that there was a close relationship between yak milk composition and intestinal microbiota. Metabolic pathway analysis found that different genera and key enzymes of methane and short-chain fatty acid metabolic pathways differed in their responses to environmental factors. Based on the above analysis, a model about environmental factors, intestinal bacteria and the flavor of yak milk was developed. The results provided a reference for the study of flavor substances in yak milk and a new direction for the improvement of dairy products and their derivatives. Highlights: The yak gut microbial diversity of southeastern Tibet-Qinghai Plateau is studied. The yak is divided into Enterotype 1 and Enterotype 2 according to its gut microbes. Stable enterotype is the basis for the function of different genera in the gut. Yak milk flavor is closely related to gut microbes and local environmental factors. A model based on enterotype to influence the flavor of yak milk is constructed.